Porous magnesium/PLGA composite scaffolds for enhanced bone regeneration following tooth extraction - Brown, Andrew; Zaky, Samer; Ray, Herbert; Sfeir, Charles (Acta biomaterialia, 2015)
[Display omitted] Sixty percent of implant-supported dental prostheses require bone grafting to enhance bone quantity and quality prior to implant placement. We have developed a metallic magnesium particle/PLGA composite scaffold to overcome the limitations of currently used dental bone grafting materials. This is the first report of porous metallic magnesium/PLGA scaffolds synthesized using a solvent casting, salt leaching method. We found that incorporation of varying amounts of magnesium into the PLGA scaffolds increased the compressive strength and modulus, as well as provided a porous structure suitable for cell infiltration, as measured by mercury intrusion porosimetry. Additionally, combining basic-degrading magnesium with acidic-degrading PLGA led to an overall pH buffering effect and long-term release of magnesium over the course of a 10-week degradation assay, as measured with inductively coupled plasma–atomic emission spectroscopy. Using an indirect proliferation assay adapted from ISO 10993:5, it was found that extracts of medium from degrading magnesium/PLGA scaffolds increased bone marrow stromal cell proliferation in vitro, a phenomenon observed by other groups investigating magnesium’s impact on cells. Finally, magnesium/PLGA scaffold biocompatibility was assessed in a canine socket preservation model. Micro-computed tomography and histological analysis showed the magnesium/PLGA scaffolds to be safer and more effective at preserving bone height than empty controls. Three-dimensional magnesium/PLGA composite scaffolds show promise for dental socket preservation and also, potentially, orthopedic bone regeneration. These scaffolds could decrease inflammation observed with clinically used PLGA devices, as well as enhance osteogenesis, as observed with previously studied magnesium devices.